Excellent strength/ductility synergy by optimization of post-weld heat treatment for gas metal arc welded CoCrFeMnNi high entropy alloys with 410 stainless filler wire: High-throughput thermodynamic modelling with experimental validation - Jiajia Shen; Rae Eon Kim; Jingjing He; Jin Yang; J.G. Lopes; Zhi Zeng; N. Schell; Hyoung Seop Kim; J.P. Oliveira (Materials & Design)
Post-weld annealing is a promising method for enhancing the performance of welded joints. However, traditional trial-and-error approaches are often time-consuming and inefficient, limiting their application in industrial production. To overcome this challenge, this study integrates high-throughput thermodynamic simulation techniques with a custom Python script to rapidly screen annealing temperatures for GMAWed CoCrFeMnNi high entropy alloy welded joints with ERNiMo-410 filler wire. By employing a combination of microstructural characterizations (such as Electron Backscatter Diffraction (EBSD) and Synchrotron X-ray Diffraction (SXRD)) and mechanical testing (including hardness testing and tensile Digital Image Correlation (DIC) analysis), the study validates the effects of selected annealing temperatures on the microstructure evolution and mechanical behavior of the welded joints. The results demonstrate that the optimized annealing temperature significantly enhances the uniformity of the microstructure and increases elongation at fracture by approximately sevenfold to 43.1 %, while maintaining comparable yield and ultimate strengths. This study highlights the potential industrial value of this method, offering an efficient and scientific approach for optimizing welded joint performance.